ANALYZING GLOBAL CROP TRADE PATTERNS AND REGIONAL DIFFERENTIATION IN THE FACE OF CLIMATE CHANGE: A CLUB CONVERGENCE APPROACH - Fatih KAPLAN; Ali Rıza AKTAŞ; Ahmet KOLUMAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Given the impacts of global climate change, foreign trade in crops is likely to face a number of challenges. It is therefore necessary to assess the foreign trade of crops from a global perspective. This study employs the club convergence analysis by Phillips and Sul to understand the extent to which export markets of crops are differentiated across countries and the differential impact across product groups. The analysis considers codes 6-14 of the 2-digit internationally harmonized system classification, which covers crop exports of countries over the period 1990-2022. The results of the analysis show that crop exports are regionally differentiated between coastal and continental regions, with 10 countries acting distinctively with other country groups in different product groups, clearly demonstrating the differentiation between countries. In addition, the study examines wheat-grain exports as a case study. We observed that most countries with significant shares in wheat-grain production and trade are in the same clubs, that is, they act together.